Variable Selection in Clustering for Sanitation Access Analysis in East Java Supporting SDG 6 - Mohammad Dian Purnama (Engineering, MAthematics and Computer Science Journal (EMACS), 2026)
To have sanitation we need to think about a few things to make people healthy and help the world be a better place. This study is trying to figure out how people in East Java get to use sanitation. We are looking at an important things that help us understand how people use sanitation. We used a method called clustering to see how different cities and districts in East Java are doing. This study utilized a set of six variables, encompassing the five pillars of community-based total sanitation (STBM). The variables employed following the selection process include awareness of open defecation (SBS), awareness of hand washing with soap (CPTM), and drinking water and food management (PAMMRT). The resulting in this study has three distinct clusters, each reflecting different levels of sanitation across cities and districts in East Java. However, the clustering is important to recognize that the excluded variables maintain considerable value as indicators established by the government. Furthermore, to its capacity to implement the variable selection method in the context of clustering, it is anticipated that this research will serve as a valuable resource for policymakers, providing them with a framework to prioritize specific areas in their efforts to enhance sanitation access for the purpose of achieving sustainable development.